Litvins as a Medieval Baltic-Slavic Ethnic Group in Kastuś Tarasaŭ's Novel “The Pursuit of Grunwald” - Khalipov, Victor (Slavica, 2026)
Ethnically colored characters based on stereotypical representations of different peoples occupy an important place in the fiction of any nation. At the same time, works of art may depict not only representatives of modern nations, but also those of ethnic groups that have now disappeared, and sometimes even those that never existed at all. A special literary discipline, imagology, is concerned with the study of this issue. In contemporary Belarusian literature, the Litvin ethnotype occupies an important place, as it is a relevant component of certain types of modern Belarusian identity. Its presence is particularly noticeable in works on historical themes. One such text, significant for the national literary tradition, is Kastuś Tarasaŭ's novel The Pursuit of Grunwald (1986), thematically devoted to the Battle of Grunwald in 1410 between the combined forces of Poland and Lithuania and the knights of the Teutonic Order. In this work, the imago of the Litvin occupies a fairly clearly defined position as the self-image, serving to describe his own people and his homeland in the past, in relation to which characters of all other nationalities are positioned as hetero-images. In Kastuś Tarasaŭ's work,  Lithuanians are a Slavic-speaking ethnic group of mixed Baltic-Krivich origin, diversified in terms of religion (Catholics, Orthodox Christians, and pagans), whose representatives make up the military and political elite of the Grand Duchy of Lithuania. The author attributes the following characteristics to them: brave, harsh, cruel, stubborn, persistent, fierce, reckless, short-sighted, and unreasonable. These traits do not fully correlate with the current stereotypical perceptions of modern Belarusians about themselves, which had developed by the end of the 20th century.